A Comparison of PlayerLoadTM and Heart Rate during Backwards and Forwards Locomotion during Intermittent Exercise in Rugby League Players - Matthew R. Barnes; Joshua H. Guy; Nathan Elsworthy; Aaron T. Scanlan (Sports, 2021)
Limited research has examined the demands of backward locomotion at various speeds using common load monitoring metrics in team sport athletes. Consequently, this study compared the external and internal loads between backward and forward locomotion during intermittent exercise in team sport athletes. Semi-professional, male rugby league players (n = 29) completed the same exercise protocol on two occasions in backward and forward directions. On each occasion, participants performed separate 20 m trials at self-selected walking, jogging, running, and sprinting speeds and then completed a 15 min modified Loughborough intermittent shuttle test (mLIST). Common external and internal load metrics were gathered across testing. Faster speeds (p < 0.001) were attained at all speeds during forward locomotion in the 20 m trials. Non-significant differences in accumulated PlayerLoadTM were found between directions across the mLIST; however, higher relative (per min) PlayerLoadTM (p < 0.001) was apparent during backward locomotion when walking and during forward locomotion when sprinting during the mLIST. RPE and mean heart rate were higher (p < 0.001) during backward locomotion across the mLIST. These data highlight the unique loading patterns experienced during backward locomotion and suggest practitioners should consider the discernment in loading imposed between backward and forward locomotion when measuring athlete demands using common metrics.